Injury-induced interleukin-1 alpha promotes Lgr5 hair follicle stem cells de novo regeneration and proliferation via regulating regenerative microenvironment in mice - Guang Yang; Haiyan Chen; Qun Chen; Jiayi Qiu; Mulan Qahar; Zhimeng Fan; Weiwei Chu; Edward E. Tredget; Yaojiong Wu (BMC, 2023)
Abstract Background The hair follicles (HFs) are barely regenerated after loss in injuries in mammals as well as in human beings. Recent studies have shown that the regenerative ability of HFs is age-related; however, the relationship between this phenomenon and the stem cell niche remains unclear. This study aimed to find a key secretory protein that promotes the HFs regeneration in the regenerative microenvironment. Methods To explore why age affects HFs de novo regeneration, we established an age-dependent HFs regeneration model in leucine-rich repeat G protein-coupled receptor 5 (Lgr5) + /mTmG mice. Proteins in tissue fluids were analyzed by high-throughput sequencing. The role and mechanism of candidate proteins in HFs de novo regeneration and hair follicle stem cells (HFSCs) activation were investigated through in vivo experiments. The effects of candidate proteins on skin cell populations were investigated by cellular experiments. Results Mice under 3-week-old (3W) could regenerate HFs and Lgr5 HFSCs, which were highly correlated with the immune cells, cytokines, IL-17 signaling pathway, and IL-1α level in the regeneration microenvironment. Additionally, IL-1α injection induced de novo regeneration of HFs and Lgr5 HFSCs in 3W mouse model with a 5 mm wound, as well as promoted activation and proliferation of Lgr5 HFSCs in 7-week-old (7W) mice without wound. Dexamethasone and TEMPOL inhibited the effects of IL-1α. Moreover, IL-1α increased skin thickness and promoted the proliferation of human epidermal keratinocyte line (HaCaT) and skin-derived precursors (SKPs) in vivo and in vitro, respectively. Conclusions In conclusion, injury-induced IL-1α promotes HFs regeneration by modulating inflammatory cells and oxidative stress-induced Lgr5 HFSCs regeneration as well as promoting skin cell populations proliferation. This study uncovers the underlying molecular mechanisms enabling HFs de novo regeneration in an age-dependent model.